Transformasi Fragmen Al-Qur’an dalam Magi: Studi atas Majmu’atul-Munawwar karya KH. Syafiq Munawwar - Siddiq Abdur Rozzaq (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2020)
The Qur’an is uniquely presented in magical culture. Most people who consider the Qur’an was final and systematic, in the magical culture the Qur’an comes with a variety of forms, different arrangements of general habits, and is used for various practical needs. In contrast to the hafiz-oriented paradigm of memorizing and preserving the Qur’an, Majmu’atul-Munawwar offers a magical perspective that transforms fragments of the Qur’an in a unique form. So, how is the quranic fragment transformation in the magical culture of Majmu’atul-Munawwar? This research applies William A. Haviland’s theory. He says that cultural elements transformed into four mechanisms: discovery, diffusion, cultural loss, and acculturation. This research explains that the quranic fragment in the Majmu’atul-Munawwar can be categorized by two: minor and major. The final form of the Quran in the Mushaf Usmani reconstructed in magical culture. Quranic fragment in Majmu’atul-Munawwar shows that the Qur’an always been transformed in different cultural spaces. Therefore the transformation of the Qur’an is a need.